Analisis Pengaruh Transformasi Digital pada Inovasi Strategi Pemasaran Perguruan Tinggi Swasta (PTS): Analisis Pengaruh Transformasi Digital pada Inovasi Strategi Pemasaran Perguruan Tinggi Swasta (PTS) - Pratama, Gede Yudha Anugerah; Prasiani, Ni Komang; Sulistio, Gabriella Rosemary (CV. ITTC INDONESIA, 2024)
Background: Digital transformation in Private Higher Education Institutions (PTS) has become an important factor in increasing marketing strategy innovation, expanding institutional appeal, and strengthening engagement with prospective students. Objective: This study aims to explore the factors that drive and inhibit the implementation of digital transformation in PTS and analyze its impact on innovation in marketing strategies. Method: The method used in this study is a systematic literature review, by analyzing relevant studies from various national journals published between 2018 and 2024. Results: The research findings show that digital transformation not only optimizes marketing strategies but also increases communication effectiveness and brand awareness through digital platforms. This study also describes the positive impact of digital transformation on increasing engagement, operational efficiency, and competitiveness of PTS. Conclusion: A conceptual framework is developed to help PTS plan and implement digital transformation strategies effectively, along with practical recommendations to overcome integration barriers. This study provides new insights and practical solutions for PTS to leverage digital transformation for greater marketing effectiveness, as well as contributing to the academic literature and guidance for practitioners and policy makers in the field of higher education.Keywords: Digital Transformation, Marketing Strategy Innovation, Private Universities.